Moderate‐intensity aerobic training reduces cardiac damage attributable to experimental iron overload in rats. Issue 8 (6th July 2021) - Ávila, Renata Andrade; Rossi, Emilly Martinelli; de Carvalho, Guilherme Mendes; Krause, Maiara; Leopoldo, André Soares; Carneiro, Maria Tereza W. D.; dos Santos, Leonardo
Abstract : New Findings: What is the central question of this study? The current literature indicates that oxidative stress plays a major role in iron overload. Although exercise is a well‐established approach to treat/prevent cardiovascular diseases, its effects on iron overload are not known. What is the main finding and its importance? Moderate‐intensity aerobic training had benefits in a rodent model of iron‐overload cardiomyopathy by improving the antioxidant capacity of the heart. After further confirmation by translational and clinical studies, we should consider using this non‐pharmacological, highly accessible and easily executable adjuvant approach allied to other therapies to improve the quality of life of iron‐overloaded patients. Abstract: Iron is an essential micronutrient for several life processes, but its excess can damage organs owing to oxidative stress, with cardiomyopathy being the leading cause of death in iron‐overloaded patients. Although exercise has long been considered as a cardioprotective tool, its effects on iron overload are not known. This study was designed to investigate the effects of moderate‐intensity aerobic training in rats previously submitted to chronic iron overload. Wistar rats received i.p. injections of iron dextran (100 mg/kg, 5 days/week for 4 weeks); thereafter, the rats were kept sedentary or exercised (60 min/day, progressive aerobic training, 60–70% of maximal speed, 5 days/week on a treadmill) for 8 weeks. At the end of the experimental period, haemodynamics were recorded and blood samples, livers and hearts harvested. Myocardial mechanics of papillary muscles were assessed in vitro, and cardiac remodelling was evaluated by histology and immunoblotting. Iron overload led to liver iron deposition, liver fibrosis and increased serum alanine aminotransferase and aspartate aminotransferase. Moreover, cardiac iron accumulation was accompanied by impaired myocardial mechanics, increased cardiac collagen type I and lipid peroxidation (TBARS), and release of creatine phosphokinase‐MB to the serum. Although exercise did not influence iron levels, tissue injury markers were significantly reduced. Likewise, myocardial contractility and inotropic responsiveness were improved in exercised rats, in association with an increase in the endogenous antioxidant enzyme catalase. In conclusion, moderate‐intensity aerobic exercise was associated with attenuated oxidative stress and cardiac damage in a rodent model of iron overload, thereby suggesting its potential role as a non‐pharmacological adjuvant therapy for iron‐overload cardiomyopathy. Abstract :